Bile acids decrease intracellular bilirubin levels in the cholestatic liver: implications for bile acid-mediated oxidative stress - Muchova, Lucie; Vanova, Katerina; Zelenka, Jaroslav; Lenicek, Martin; Petr, Tomas; Vejrazka, Martin; Sticova, Eva; Vreman, Hendrik Jan; Wong, Ronald James; Vitek, Libor (Journal of cellular and molecular medicine, 2011)
High plasma concentrations of bile acids (BA) and bilirubin are hallmarks of cholestasis. BA are implicated in the pathogenesis of cholestatic liver damage through mechanisms involving oxidative stress, whereas bilirubin is a strong antioxidant. We evaluated the roles of bilirubin and BA on mediating oxidative stress in rats following bile duct ligation (BDL). Adult female Wistar and Gunn rats intraperitoneally anaesthetized with ketamine and xylazine underwent BDL or sham operation. Cholestatic markers, antioxidant capacity, lipid peroxidation and heme oxygenase (HO) activity were determined in plasma and/or liver tissue 5 days after surgery. HepG2-rNtcp cells were used for in vitro experiments. Plasma bilirubin levels in control and BDL animals positively correlated with plasma antioxidant capacity. Peroxyl radical scavenging capacity was significantly higher in the plasma of BDL Wistar rats (210 ± 12%, P < 0.0001) compared to controls, but not in the liver tissues. Furthermore after BDL, lipid peroxidation in the livers increased (179 ± 37%, P < 0.01), whereas liver HO activity significantly decreased to 61% of control levels (P < 0.001). Addition of taurocholic acid (TCA, ≥ 50 μmol/l) to liver homogenates increased lipid peroxidation (P < 0.01) in Wistar, but not in Gunn rats or after the addition of bilirubin. In HepG2-rNtcp cells, TCA decreased both HO activity and intracellular bilirubin levels. We conclude that even though plasma bilirubin is a marker of cholestasis and hepatocyte dysfunction, it is also an endogenous antioxidant, which may counteract the pro-oxidative effects of BA in circulation. However, in an animal model of obstructive cholestasis, we found that BA compromise intracellular bilirubin levels making hepatocytes more susceptible to oxidative damage.
Keywords: cholestáza; oxidační stres; Rats, Wistar; kyselina taurocholová; Cell Line, Tumor; Bile Acids and Salts; hemová oxygenasa (decyklizující); Bilirubin; bilirubin; potkani Wistar; Cholestasis; žlučové kyseliny a soli; krysa rodu Rattus; Heme Oxygenase (Decyclizing); Intracellular Space; Animals; lidé; ženské pohlaví; játra; potkani Gunn; Humans; zvířata; Taurocholic Acid; Rats; peroxidace lipidů; Lipid Peroxidation; Rats, Gunn; Liver; nádorové buněčné linie; Female; Oxidative Stress; intracelulární prostor